Inhibition of post-trabeculectomy fibrosis via topically instilled antisense oligonucleotide complexes co-loaded with fluorouracil - Kuan Jiang; Junyi Chen; Lingyu Tai; Chang Liu; Xishan Chen; Gang Wei; Weiyue Lu; Weisan Pan (Elsevier, 2020)
Trabeculectomy is the mainstay of surgical glaucoma treatment, while the success rate was unsatisfying due to postoperative scarring of the filtering blebs. Clinical countermeasures for scar prevention are intraoperative intervention or repeated subconjunctival injections. Herein, we designed a co-delivery system capable of transporting fluorouracil and anti-TGF-β2 oligonucleotide to synergistically inhibit fibroblast proliferation via topical instillation. This co-delivery system was built based on a cationic dendrimer core (PAMAM), which encapsulated fluorouracil within hydrophobic cavity and condensed oligonucleotide with surface amino groups, and was further modified with hyaluronic acid and cell-penetrating peptide penetratin. The co-delivery system was self-assembled into nanoscale complexes with increased cellular uptake and enabled efficient inhibition on proliferation of fibroblast cells. In vivo studies on rabbit trabeculectomy models further confirmed the anti-fibrosis efficiency of the complexes, which prolonged survival time of filtering blebs and maintained their height and extent during wound healing process, exhibiting an equivalent effect on scar prevention compared to intraoperative infiltration with fluorouracil. Qualitative observation by immunohistochemistry staining and quantitative analysis by Western blotting both suggested that TGF-β2 expression was inhibited by the co-delivery complexes. Our study provided a potential approach promising to guarantee success rate of trabeculectomy and prolong survival time of filtering blebs.